The occurrence of perfluoroalkyl substances (PFAS) in drinking water in the Czech Republic: a pilot study - Jurikova, Martina; Dvorakova, Darina; Pulkrabova, Jana (Environmental science and pollution research international, 2022)
Drinking water is one of the main contributors to overall human exposure to per- and polyfluoroalkyl substances (PFAS), a broad group of environmental contaminants with arising concerns on the impact on human health; therefore, it is necessary to monitor its quality. Here, we present a solid-phase extraction-based method to determine 22 PFAS in water, using 100 mL of the sample. The instrumental analysis employing an ultra-high-performance liquid chromatography coupled with tandem mass spectrometry achieved low limits of quantification (0.025-0.25 ng/L). The validated method (recoveries 70-120% and repeatabilities ≤ 20% at tested concentrations (0.05, 0.1 and 0.5 ng/L)) was applied to 67 tap water and 31 bottled water samples collected in the Czech Republic. The most abundant compounds were perfluorononanoic acid (88% positives; 0.034-13.3 ng/L) and perfluoroheptanoic acid (23% positives; 0.035-0.106 ng/L), respectively. ∑PFAS in positive samples ranged from 0.029 to 300 ng/L (99% positives, median 2.34 ng/L) in tap water data and 0.033 to 4.48 ng/L (32% positives, median 0.097 ng/L) in bottled water samples. Current-use fluoroalkyl ethers, dodecafluoro-3H-4,8-dioxanonanoate and 11-chloroeicosafluoro-3-oxaundecane-1-sulfonate, were occasionally detected in tap. Based on the median data, PFAS intake by an adult from a tap or bottled water represented units of % of the tolerable weekly intake set by the European Food Safety Authority and therefore did not represent a severe risk. The described method and obtained first data on PFAS in the Czech drinking water provided a solid basis for an ongoing national study on the presence of PFAS in tap water.
Keywords: Tap water; Česká republika; Solid-phase extraction; fluorokarbony; Adult; PFAS; Czech Republic; Bottled water; chemické látky znečišťující vodu; Drinking Water; Fluorocarbons; Water Pollutants, Chemical; Humans; pilotní projekty; Exposure; Pilot Projects; UHPLC-MS/MS; dospělí; lidé; pitná voda